Cysteine-string protein: the chaperone at the synapse. - Chamberlain, L.H.; Burgoyne, R.D. (Journal of Neurochemistry, 2000)
Cysteine-string protein (Csp) is a major synaptic vesicle and secretory granule protein first discovered in Drosophila and Torpedo. Csps were subsequently identified from Xenopus, Caenorhabditis elegans, and mammalian species. It is clear from the study of a null mutant in Drosophila that Csp is required for viability of the organism and that it has a key role in neurotransmitter release. In addition, other studies have directly implicated Csp in regulated exocytosis in mammalian neuroendocrine and endocrine cell types, and its distribution suggests a general role in regulated exocytosis. An early hypothesis was that Csp functioned in the control of voltage-gated Ca2+ channels. Csp, however, must have an additional function as a direct regulator of the exocytotic machinery as changes in Csp expression modify the extent of exocytosis triggered directly by Ca2+ in permeabilised cells. Csps possess a cysteine-string domain that is highly palmitoylated and confers membrane targeting. In addition, Csps have a conserved "J" domain that mediates binding to an activation of the Hsp70/ Hsc70 chaperone ATPases. This and other evidence implicate Csps as molecular chaperones in the synapse that are likely to control the correct conformational folding of one or more components of the vesicular exocytotic machinery. Targets for Csp include the vesicle protein VAMP/synaptobrevin and the plasma membrane protein syntaxin 1, the significance of which is discussed in possible models to account for current knowledge of Csp function.